A HIDDEN CURRICULUM PRACTICES - Atik Kurniawati (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
This paper departs from the issue of the hidden curriculum that occurred during the last 10 years. Hidden curriculum is the practice of school education that contributes to education. Previous studies discuss the role of the state, the role of the school and the teacher's role in the practice of hidden curriculum separately.While in this paper, the researchers wanted to demonstrate the practice of hidden curriculum in a comprehensive manner by using thought Henry Giroux. This research is a case study with a qualitative approach. This research was conducted in 2019 by conducting in-depth interviews, observation and documents. The findings in this study (1) there is a contestation of values ​​due to differences in ideology trustees and teachers that are implemented in the practice of hidden curriculum, (2) The practice of hidden curriculum is done by the board of trustees behind the development of a formal curriculum, and carried out by the teacher to maintain the old identity through daily practices, (3) impacted on the delay on student achievement, because it is generally the practice of hidden curriculum support the practice of the formal curriculum, but the opposite what happened.. advice in this study is need to agree and trust between the board of trustees and school teachers in order to get maximum achievement.